Effect of Explicit Prioritization on Dual Tasks During Standing and Walking in People With Neurologic and Neurocognitive Disorders: A Systematic Review and Meta-analysis - Van Criekinge, Tamaya; Sahu, Upasana; Bhatt, Tanvi (Archives of physical medicine and rehabilitation, 2024)
•Adults with neurological disorders benefit from task prioritization instructions.•Cognitive decline negatively affects performance after explicit prioritization.•Instructions should be specific to the intended temporal or spatial motor goal.•Generic equal prioritization or lack of specific instructions still allows implicit prioritization. To examine the effectiveness of explicit task (ie, equal, motor or cognitive) prioritization during dual tasking (DT) in adults with neurologic and neurocognitive disorders (stroke, Parkinson disease [PD], multiple sclerosis, dementia, Alzheimer disease, and mild cognitive impairment). A systematic search in 4 databases (PubMed, Web of Science, Embase, and Cochrane Central) yielded 1138 unique studies published up to 2023. Forty-one experimental studies were selected that assessed the effect of explicit prioritization instructions on both motor and cognitive performance during dual-tasks related to standing and walking in selected populations. Primary outcome measures were walking speed and response accuracy. Availability of data allowed us to perform a meta-analysis on 27 of the 41 articles by using inverse variance with a random effects model. The data including design, subject characteristics, motor and cognitive tasks, prioritization, motor and cognitive outcomes, instructions, and key findings were extracted. Two assessors rated the selected studies for risk of bias and quality using the Quality Assessment Tools of the National Institutes of Health. This study examined 1535 adults who were asked to perform motor-cognitive DT in standing or walking, including 381 adults with stroke, 526 with PD, 617 with multiple sclerosis, 10 with dementia, 9 with Alzheimer disease, and 8 with mild cognitive impairment. During all prioritization instructions, participants slowed down during DT (standardized mean difference (SMD)equal=0.43; SMDmotor=0.78; SMDcognitive=0.69, P<.03) while maintaining similar response accuracy (SMDequal=0.12; SMDmotor=0.23; SMDcognitive=-.01, P>.05). However, considerable between-group heterogeneity was observed resulting in different motor and cognitive responses between pathologies. Motor prioritization was achieved in adults with PD and stroke, unlike adults with neurocognitive disorders who were negatively affected by any type DT prioritizing. The reported within-group heterogeneity revealed that effects of explicit task prioritization are dependent on motor and cognitive task complexity, and the type of instructions. Recommendations are provided to ensure accurate use of instructions during DT paradigms.